An Additional Evidence: Pecking Order Theory in Indonesia - Pratiwi, Yosi Setya; Yulianto, Arief (Management Analysis Journal, 2022)
The paper aims to determine the leverage deviation and the impact of firm size on the leverage deviation. We have collected 504 pooled data from the Indonesia Stock Exchange (IDX) from 2009 to 2020. The model estimates have been analyzed by OLS regression, where regress, the deviation of leverage, and firm size is the explanatory variable. Our spurious prevention model controls growth and tangible assets. Our finding is that the company's overleverage is greater than the under leverage of 504 units of observation. OL type companies, characterized by asset volatility with firm size and lower debt ratio, tend to follow the POT hierarchy. They prefer debt issuance over equity; the actual leverage is lower than the target leverage. In contrast, companies characterized by UL with higher volatility in assets in place with firm size and higher debt ratio than OL tend to follow the PDT hierarchy. As a result, they issue equity over debt, and then large companies issue equity in the presence of information asymmetry. It is possible that the modal structure is dynamic and will require testing of time series or data panels. We leave that explicit analysis for future research.